1999
DOI: 10.1161/01.atv.19.9.2141
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of the Prostanoid EP 3 Receptor Reduces Myocardial Infarct Size in Rodents

Abstract: Abstract-The cardioprotective effects of E-type prostaglandins (EPs) have been attributed to vasodilatation, inhibition of platelet and neutrophil function (EP 2 mediated), and an unknown "cytoprotective effect." We have hypothesized that selective activation of EP 3 receptors may cause cardioprotection. The prostanoid derivative ONO-AE-248 selectively binds to murine EP 3␣ receptors expressed in Chinese hamster ovary (CHO) cells (K i , 15 nmol/L) and prevents the rise in cAMP caused by forskolin in CHO cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 24 publications
(31 reference statements)
1
40
0
Order By: Relevance
“…This enhanced prostanoid availability/activity may contribute to the HDL-mediated cardioprotection, by acting directly on cardiomyocytes (Zacharowski et al 1999) and/or by inhibiting cardiac TNF-α production (Shinomiya et al 2001); (3) HDL may reduce the expression of TLR 4 (Van Linthout et al 2011), which has recently been shown to play an important role in cardiac apoptosis in diabetic cardiomyopathy.…”
Section: Human Apo A-i Gene Transfer Reduces Diabetes-associated Cardmentioning
confidence: 99%
“…This enhanced prostanoid availability/activity may contribute to the HDL-mediated cardioprotection, by acting directly on cardiomyocytes (Zacharowski et al 1999) and/or by inhibiting cardiac TNF-α production (Shinomiya et al 2001); (3) HDL may reduce the expression of TLR 4 (Van Linthout et al 2011), which has recently been shown to play an important role in cardiac apoptosis in diabetic cardiomyopathy.…”
Section: Human Apo A-i Gene Transfer Reduces Diabetes-associated Cardmentioning
confidence: 99%
“…This finding implies a direct role for EP3 receptors in various neurodegenerative disorders, such as stroke and Alzheimer disease. In addition, Zacharowski and colleagues (Zacharowski et al, 1999) reported that ONO-AE-248, a selective EP3 agonist, prevented the forskolin-induced increase in cAMP in CHO cell lines. Recently, Yamazaki et al (2005) showed that EP3 receptor protein expression was significantly elevated in placenta 24 h after ischemia-reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…Because previous studies have shown that the EP3 receptor significantly affects outcomes after ischemia-reperfusion injury in peripheral organs (Martin et al, 2005;Yamazaki et al, 2005;Zacharowski et al, 1999), our goal in this study was to determine the role of EP3 in brain injury induced by ischemia-reperfusion injury. Therefore, we investigated the effects of the EP3 agonist ONO-AE-248 [Ki estimated at 10000, 3700, 7.5, and 4200 for EP1, EP2, EP3, and EP4, respectively (Kiriyama et al, 1997;Narumiya and FitzGerald, 2001;Suzawa et al, 2000)] on middle cerebral artery occlusion (MCAO)-induced infarct volume, relative cerebral blood flow (CBF), mean arterial blood pressure (MABP), and other physiological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…ONO-AE-248 is an agonist at the EP3␣ receptor that is coupled to G i and decreases cAMP (Zacharowski et al, 1999). When the knee joint was normal, the EP3␣ agonist did not significantly change the responses of the neurons to mechanical stimulation of the knee joint and the ankle (Fig.…”
Section: Different Pattern Of Effects Of Ep Agonists During Peripheramentioning
confidence: 94%
“…The following agonists were used: the EP1 receptor agonist ONO-DI-004 [doses in the present experiments were 0.1 ng/l (2.36 M) to 100 ng/l (2.36 mM); Ono Pharmaceutical, Osaka, Japan], the EP2 receptor agonist butaprost [doses in the present experiments were 0.1 ng/l (2.44 M) to 100 ng/l (2.44 mM); Cayman Chemical, Ann Arbor, MI], the EP3␣ receptor agonist ONO-AE-248 [doses in the present experiments were 1 ng/l (26.28 M) to 100 ng/l (2.628 mM); Ono Pharmaceutical], and the EP4 receptor agonist ONO-AE1-329 [doses in the present experiments were 1 ng/l (21.9 M) to 100 ng/l (2.199 mM); Ono Pharmaceutical]. The compounds ONO-DI-004, ONO-AE-248, and ONO-AE1-329 have been generated and characterized recently and have been used in different studies (Yamamoto et al, 1999;Zacharowski et al, 1999;Suzawa et al, 2000;Maruyama et al, 2001;Shinomiya et al, 2001 (Yamamoto et al, 1999;Suzawa et al, 2000). EC 50 values are as follows: ONO-DI-004, 0.42 M at the EP1 receptor; ONO-AE-248, 0.0052 M at the EP3␣ receptor; ONO-AE1-329, 0.0031 M at the EP4 receptor (Yamamoto et al, 1999).…”
Section: In Vivo Experimentsmentioning
confidence: 99%